Effect of removal of endogenous non-starch components on the structural, physicochemical properties, and in vitro digestibility of highland barley starch. (August 2021) - Yang, Yueyue; Jiao, Aiquan; Zhao, Shuna; Liu, Qing; Fu, Xi; Jin, Zhengyu
Abstract: Highland barley (HB) is a kind of slow-digesting grain. The effects of endogenous non-starch components on the digestibility of highland barley starch (HBS) are worth exploring. In this study, the effects of non-starch components on the structure, physicochemical and digestibility of HBS were studied by removing β-glucan, proteins and lipids individually and in pairs. The results showed that, all removal treatments led to an increase in the swelling power of the HBS and changes in its pasting properties, causing its easier gelatinisation and subsequent digestion. The effects of the removal of multiple components on the digestion and physicochemical properties of HBS were more significant than those corresponding to that of a single. The effect order of a single non-starch component on starch digestibility is: lipids < β-glucans < proteins. Regarding the multiple, the lowest SDS was induced by the removals of lipid and protein (actually, the protein, β-glucan and lipids were all removed), and the lowest RS was induced by the removal of proteins. The changes in the physiochemical and digestion properties caused by the removal of the non-starch components were significantly correlated; the swelling power was significantly and positively correlated with the glucose concentration at the end of digestion, and the sum of SDS and RS content was positively correlated with the ratio of 1022/995 cm −1 . In conclusion, these results reveal the internal factors affecting the slow digestion characteristics of HB from the perspective of endogenous non-starch components while providing important reference values of these components in slow-digesting diets. Graphical abstract: Image 1 Highlights: Highland barley starch (HBS) gelatinized easily after removing non-starch components. Removing non-starch components increased the in vitro digestibility of HBS. The lowest SDS was induced by the removals of lipid and protein. The lowest RS was induced by the removal of proteins. The physiochemical properties of HBS were significantly correlated to digestibility.